2017
DOI: 10.14429/djlit.37.3.10567
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Resources and Services by Faculty Members and Students of Fiji National University

Abstract: The effectiveness of electronic resources and services in select campuses of Fiji National University Library on the basis of users' satisfaction is evaluated. A survey method was employed to conduct this research. Out of sixteen campus libraries of FNU, the researcher selects eight libraries from different division of Fiji in the user's survey. 150 well-structured questionnaires were distributed to gather information related to uses of electronic resources and services. The 140 filled questionnaireswere colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Other challenges mentioned were slow download speeds, the server being down sometimes and some journals displaying content from only the past two years. The latter challenge was mentioned previously in a study done in Saudi Arabia (Alhadeeb and Alanz, 2013), as were some of the other challenges, like slow downloads in Fiji (Sohail and Ahmad, 2017) and Kuwait (Al-Ansari, 2006).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Other challenges mentioned were slow download speeds, the server being down sometimes and some journals displaying content from only the past two years. The latter challenge was mentioned previously in a study done in Saudi Arabia (Alhadeeb and Alanz, 2013), as were some of the other challenges, like slow downloads in Fiji (Sohail and Ahmad, 2017) and Kuwait (Al-Ansari, 2006).…”
Section: Resultsmentioning
confidence: 83%
“…In Fiji, Sohail and Ahmad (2017) conducted a study on the use of ER and services by faculty and students of Fiji National University Library. The researchers surveyed eight of 16 libraries, and their results revealed a growing awareness of ER and services in the field of academic research.…”
Section: Related Studiesmentioning
confidence: 99%
“…That is, personal differences may influence the effect of job boredom. Several studies showed that age, intelligence, gender, and tenure are related to job boredom (Drory, 1982;Hill, 1975;Kass et al, 2001;Sohail et al, 2012). Conflict results were shown regarding relationship between age and job boredom.…”
Section: Job Boredommentioning
confidence: 99%
“…A study of heavy truck drivers found that younger workers were more likely to get bored than older ones (Drory, 1982). On the contrary, older workers were more likely to be bored than younger ones among university employees (Sohail et al, 2012). Related to intelligence, a few researchers found that more intelligent workers were likely to get bored when they were doing less-challenging work (Drory, 1982;London et al, 1972).…”
Section: Job Boredommentioning
confidence: 99%
“…An academic library is responsible for providing academic information to the university community; therefore, it is of importance for the university to ensure that its library is fully equipped with ICTs and ELRs. Worldwide, there is a growing interest in the use of ELRs among scholars and students (Sohail & Ahmad 2017). Academic libraries are subscribing to ELRs, such as electronic books (e-books), electronic journals (e-journals), electronic theses and online databases, to enable scholars, researchers, and students to have access to information required for academic purposes.…”
Section: Introductionmentioning
confidence: 99%